Factors associated with teenage pregnancy at Dwarsloop Local Area Clinics, Bushbuckridge Sub-district, Mpumalanga Province - Mnisi, Evodia Zandile (My University, 2019)
Refer to document
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Teenage pregnancy; Teenage; Contraceptive; Access; Contraception; Teenage pregnancy; Teenagers -- Sexual behavior; Clinics -- South Africa -- Mpumalanga